IMPLEMENTASI MODEL PROBLEM BASED LEARNING BERMEDIAKAN SLIDE PRESENTASI BERBASIS UNJUK KERJA UNTUK MENINGKATKAN KOMPETENSI PENGETAHUAN IPA - ARNAWA, ADI (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
This study aimed to improve competency in science knowledge through the implementation of the Problem Based Learning Model providing performance-based presentation slides in online learning. This research is a classroom action research conducted in two cycles. The research subjects were students of SD No. 3 Legian, totaling 36 students. Science knowledge competency data were collected using tests. The collected data were analyzed using quantitative descriptive statistical analysis. The results showed that in the pre-cycle the average percentage of competence in science knowledge was 64% categorized as low with classical completeness reaching 25%. After improving the learning process in the first cycle, the average percentage of competency in science knowledge became 68% categorized as moderate with classical completeness reaching 67%. In the second cycle, it increased to 81% categorized as high with classical completeness reaching 83%. Based on the results of this study, it can be concluded that the implementation of the Problem Based Learning model providing performance-based presentation slides in online learning can improve the competence of science knowledge of students of SD No. 3 Legian Academic Year 2020/2021